2014 IEEE 22nd Annual International Symposium on Field-Programmable Custom Computing Machines 2014
DOI: 10.1109/fccm.2014.25
|View full text |Cite
|
Sign up to set email alerts
|

On Hard Adders and Carry Chains in FPGAs

Abstract: Abstract-Hardened adder and carry logic is widely used in commercial FPGAs to improve the efficiency of arithmetic functions. There are many design choices and complexities associated with such hardening, including circuit design, FPGA architectural choices, and the CAD flow. There has been very little study, however, on these choices and hence we explore a number of possibilities for hard adder design. We also highlight optimizations during front-end elaboration that help ameliorate the restrictions placed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…We argue that this is not the best approach to discover carry chains: mainly, (1) it is impossible to discover chains in circuits where adders are implemented at the gate level, (2) misses opportunities of using full adders or small-bitwidth adders in other situations not immediately derived from explicit additions, and (3) removes these components from the sight of logic synthesis, thus preventing even some basic logic optimisations such as constant propagation. Instantiating hardened adders before logic optimisation may easily lead to redundant or unnecessary logic not being eliminated [6]. Additionally, in the VTR flow, (4) the adders presented as black boxes prevent the synthesizer ABC from correctly modelling the critical path of the circuit.…”
Section: B Discovering Carry Chainsmentioning
confidence: 99%
See 1 more Smart Citation
“…We argue that this is not the best approach to discover carry chains: mainly, (1) it is impossible to discover chains in circuits where adders are implemented at the gate level, (2) misses opportunities of using full adders or small-bitwidth adders in other situations not immediately derived from explicit additions, and (3) removes these components from the sight of logic synthesis, thus preventing even some basic logic optimisations such as constant propagation. Instantiating hardened adders before logic optimisation may easily lead to redundant or unnecessary logic not being eliminated [6]. Additionally, in the VTR flow, (4) the adders presented as black boxes prevent the synthesizer ABC from correctly modelling the critical path of the circuit.…”
Section: B Discovering Carry Chainsmentioning
confidence: 99%
“…Additionally, suboptimal mapping decision can be made by assigning adders to carry chains before technology mapping (i.e., design step that transforms the gate-level description of the input into a network of LUTs). Luu et al [6] have recently shown that using carry chains provides an average speed up of approximately 15% for an area penalty of approximately 5%. However, in some benchmarks using carry chains led to slower and bigger circuits.…”
Section: Introductionmentioning
confidence: 99%
“…Columns of CLBs are replaced by heterogeneous blocks such as memory banks and digital signal processing (DSP) blocks. BLEs comprise of fracturable LUTs [25] and hard carry chains [26]. Local routing architecture also interconnects adjacent CLBs to provide highways between neighbors [27], [28].…”
Section: A Island-style Fpga Fabricmentioning
confidence: 99%
“…In this work, we prototype our technique focusing on the adder compound operator. Luu et al explored using hardened adders in VTR to improve efficiency of arithmetic operations as they are a rather small and prevalent circuit [10]. In that work, the authors measured an overall performance improvement of 15%.…”
Section: Related Workmentioning
confidence: 99%